THE CONSTRUCTION OF THE IDEAL MALE BODY MASCULINITY IN THE MISTER INTERNATIONAL PAGEANT - Habib, Muhammad Alhada Fuadilah; Ratnaningsih, Asik Putri Ayusari; Nisa, Kanita Khoirun (Journal of Urban Sociology, 2019)
As Michael Foucault had said that the human body is not really free; the concept of the body as well as the concept of the human sexuality in fact are ruled by and obey the great power behind them. A great narrative about the body and also the sexuality that has been agreed by societies, consciously or unconsciously has successfully dictated societies’ point of view in placing their body and sexuality. The concept of a male body that has been characterized by its perfunctory appearance, in the sense of not necessary to primp, actually is a great narrative that is considered as a true necessity. This topic is unique and interesting to study because Mister International pageant as the representation of world’s male masculinity offers the different great narrative masculinity concept that has been shackling the traditional masculinity concept of Indonesian society. This study will analyze the signs of masculinity shown in Mister International pageant as the ideal men’s quest in the world. The result of this study indicates that the ideal male masculinity constructed in Mister International pageant if viewed from the concept of traditional sexuality is a combination between the concept of femininity and the concept of masculinity that then brought out to a new terminology about the concept of masculinity called as metrosexual. The concept of masculinity constructed by this ideal men’s quest in the world, if examined by Herbert Marcuse’s point of view, actually is a concept uniformity of the world's ideal male body in one dimension. Furthermore, the great narrative behind this uniformed ideal male construction is a world’s major capitalists’ project to expand their market share, especially male cosmetics and clothes products.Keywords: Construction, Masculinity, Ideal Male Body, One-Dimensional Man.